Sebaran Pertumbuhan Alami Matoa (Pometia Pinnata) Berdasarkan Ketinggian Tempat di Kelompok Hutan Desa Badaro Kecamatan Modayag Kabupaten Bolaang Mongondow Timur - Amon, Hendra; Rempas, Robby DJ (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study was to determine the distribution of natural growth at each growth level of matoa (Pometia pinnata) based on altitude in the forest group of Badaro Village, Modayag District, East Bolaang Mongondow Regency. The method used in this study is the survey method, while data collection uses the plot sampling method technique in the research area. The results of the study showed that in the Badaro Village Forest Group, natural stands of Pometia pinnata were spread from an altitude of 300 - 700 m above sea level. The largest number was in the sapling phase with 15 individuals, while the smallest number was in the tree phase with 6 individuals. The number of Pometia pinnata individuals in the seedling phase was 2 individuals at an altitude of 300 m above sea level, 3 individuals at an altitude of 400 m above sea level, 2 individuals at an altitude of 500 m above sea level, 2 individuals at an altitude of 600 m above sea level, and 1 individual at an altitude of 700 m above sea level. The number of Pometia pinnata individuals in the sapling phase was 1 individual at an altitude of 300 m above sea level, 4 individuals at an altitude of 400 m above sea level, 4 individuals at an altitude of 500 m above sea level, 2 individuals at an altitude of 600 m above sea level, and 4 individuals at an altitude of 700 m above sea level. The number of Pometia pinnata individuals in the pole phase was 2 individuals at an altitude of 300 m above sea level, 1 individual at an altitude of 400 m above sea level, 1 individual at an altitude of 500 m above sea level, 1 individual at an altitude of 600 m above sea level, and 2 individuals at an altitude of 700 m above sea level. Meanwhile, the number of Pometia pinnata individuals in the tree phase is 1 individual at an altitude of 300 meters above sea level, 2 individuals at an altitude of 400 meters above sea level, 1 individual at an altitude of 500 meters above sea level, 1 individual at an altitude of 600 meters above sea level, and 1 individual at an altitude of 700 meters above sea level. The distribution of natural growth of matoa (Pometia pinnata) at each growth phase based on altitude is the same or even at each altitude, but the higher the location, the fewer individuals are found.